Moderate-Intensity Aerobic Exercise Restores Appetite and Prefrontal Brain Activity to Images of Food Among Persons Dependent on Methamphetamine: A Functional Near-Infrared Spectroscopy Study - Wang, Hongbiao; Chen, Yifan; Li, Xiawen; Wang, Jiakuan; Zhou, Yu; Zhou, Chenglin (Frontiers in Human Neuroscience, 2019)
The brain prefrontal control system is critical to successful recovery from substance use disorders, and the prefrontal cortex (PFC) regulates striatal reward-related processes. Substance-dependent individuals exhibit increased response to drug rewards and decreased response to natural, nondrug rewards. Short-term aerobic exercise can ameliorate craving and inhibitory deficits in methamphetamine users, but the effect of exercise on food reward is unknown. This study used functional near-infrared spectroscopy (fNIRS) to measure the effects of moderate- and high-intensity short-term aerobic exercise on prefrontal activity related to food images and recorded the subjective feelings of appetite in methamphetamine-dependent users. In total, 58 men who met the Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition) criteria for methamphetamine dependence, with a mean (SD) body mass index of 24.7 (3.5) kg/m2 and age of 30.2 (5.1) years, were randomly assigned to one of two exercise groups: moderate intensity (n = 28; 65%–75% of maximum heart rate) and high intensity (n = 28; 76%–85% of heart rate maximum). Each group also performed a resting control session for 35 min 1 week before or after the exercise, in a counterbalanced order. Mean oxygenated hemoglobin concentration changes in the PFC when viewing visual food cues were assessed by fNIRS, and subjective feelings of appetite were self-rated using visual analog scales after moderate- or high-intensity aerobic exercise and after the resting control session. Functional data were collected using a continuous-wave NIRS device, with eight sources and seven detectors placed on the forehead, resulting in 20 channels covering PFC regions. We found that moderate-intensity aerobic exercise significantly increased both activation of the left orbitofrontal cortex to images of high-fat food (P = 0.02) and subjective sensations of hunger (F(1,54) =7.16, P = 0.01). To our knowledge, this study provides the first evidence that moderate-intensity aerobic exercise increases orbitofrontal cortex activity associated with high-fat food images and stimulates appetite in methamphetamine-dependent individuals. These changes suggest that exercise may reestablish the food reward pathway hijacked by drugs and restore sensitivity to natural rewards. This evidence may contribute to the development of specific exercise programs for populations with methamphetamine dependence.